The "Elderly" in Medicine: Ethical Issues Surrounding This Outdated and Discriminatory Term - Javad Hekmat-panah MD (SAGE Publishing, 2019)
The objective of this study was to investigate and describe how the use of the term "elderly" contributes to bias and problems within the medical system. A systematic review of the relevant literature and history was conducted. The term "elderly" does not define age accurately and carries bias and prejudice that lead to harm through discriminatory practices, institutional prejudices, and "ageist" policies in society and medicine. Doctors and healthcare providers seldom intentionally try to harm any patient, but might do so through unconscious anti-elderly bias. Studies indicate that medical students already demonstrate anti-elderly bias; researchers may lump patients aged 65 and over together, confounding specific information needed for individualized treatments; and out of unwarranted concern, medical and surgical treatments may be denied, despite minimal increased risk of mortality. When the cost of healthcare rises, it is the elderly against whom rationing is suggested. The term "elderly" has no place in medicine. Anti-elderly health care rationing is as unethical as rationing targeted against any group. It is reverse paternalism to make rules that limit others' medical care, happiness, and life span without their consent. Medicine is the science and art of individual communication, evaluation and treatment. Once we deny care to any one group, we open the door to denial to others.